Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/jcsm.12059
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of anorexia in the cancer cachexia syndrome

Abstract: Anorexia is commonly present in persons with cancer and a major component of cancer cachexia. There are multiple causes of anorexia in cancer. Peripherally, these can be due to (i) substances released from or by the tumour, e.g. pro-inflammatory cytokines, lactate, and parathormone-related peptide; (ii) tumours causing dysphagia or altering gut function; (iii) tumours altering nutrients, e.g. zinc deficiency; (iv) tumours causing hypoxia; (v) increased peripheral tryptophan leading to increased central seroton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(131 citation statements)
references
References 211 publications
(364 reference statements)
2
117
0
8
Order By: Relevance
“…A large body of evidence demonstrates that the hypothalamus is a critical driver of cachexia, transducing systemic inflammatory messages stemming from acute and chronic disease processes into a local and paracrine inflammatory response in the central nervous system 23, 24, 25. Consistent with this evidence, KPC induces an array of genes responsive to inflammatory stimuli in the hypothalamus.…”
Section: Resultsmentioning
confidence: 79%
“…A large body of evidence demonstrates that the hypothalamus is a critical driver of cachexia, transducing systemic inflammatory messages stemming from acute and chronic disease processes into a local and paracrine inflammatory response in the central nervous system 23, 24, 25. Consistent with this evidence, KPC induces an array of genes responsive to inflammatory stimuli in the hypothalamus.…”
Section: Resultsmentioning
confidence: 79%
“…Inflammation is thought to be a primary cause of loss of appetite (anorexia) in cancer cachexia, a syndrome characterized by systemic inflammation, negative protein and energy balance, and progressive loss of adipose tissue and skeletal muscle mass [68,74]. Various studies showed that n-3 PUFA supplementation improves anorexia via an anti-inflammatory effect, evident by inhibition of cytokine production and by promoting the release of hypothalamic orexigenic peptides and neurotransmitters to increase appetite [75].…”
Section: Discussionmentioning
confidence: 99%
“…Cachexia is defined as a loss of lean mass due to inflammatory cytokines (55,56). It also has anorexia, anemia, and low albumin (57). Persons with cachexia have a loss of muscle out of proportion to fat loss.…”
Section: Figure 2 Mechanisms By Which Dysphagia Causes Undernutritionmentioning
confidence: 99%